O pensamento computacional na resolução de problemas discretos : seu valor didático à luz da teoria dos registros de representação semiótica - Tavares, Lucas Calegari (2024)
Research with a qualitative approach and exploratory objective that investigated the following research problem: "What is the didactic value of solving discrete problems using computational thinking for learning recursive functions?". The general objective is to verify the didactic value of solving discrete problems using computational thinking to learn recursive functions. Its theoretical reference is the Theory of Semiotic Representation Records. The research defines the concept of didactic value, using the concept of record coordination. In the bibliographical research, we sought theoretical references that involve activities with aspects of unplugged computing, with no intention of using computational thinking as a heuristic approach to problem solving. The data was found through field research and in solving activities through the researcher. In the field research, an activity was carried out with students in the 9th year of Final Years Elementary School. The research identifies the representation registers used in solving discrete problems involved in recursion, classifying the gaps between them regarding congruence and, in the case of auxiliary representations, their functions according to Moretti and Baerle's classification. It is concluded that activities with didactic value encouraged the combination of different semiotic registers, enabling a better understanding of the mathematical objects studied. This approach can guide other education professionals in creating activities that enhance students' mathematical learning in Basic Education